"Fairtradization": a performative perspective on fair trade markets and the role of retail settings in their enactment. Issue 6 (2nd November 2017) - Geysmans, Robbe; de Krom, Michiel P. M. M.; Hustinx, Lesley
ABSTRACT: In line with the Callonian approach in economic sociology, this paper introduces the concept of "fairtradization" to analyze the assemblages of human agents, material devices, and discourses through which the fair trade market is enacted. We argue that the retail setting is a key site for the enactment of particular versions of "fair trade, " focusing on a case study of the newly designed world shops in Flanders (Belgium). We reveal that the new shop design – aimed to address particular overflows resulting from the mainstreaming of fair trade – constitutes a multivocal shopping environment that enables four analytically distinct enactments of fair trade shopping. Our analytical approach opens up a more dynamic and complex understanding of fair trade beyond the unidirectional diagnosis of mainstreaming. More generally, it provides support for a radically performative view of consumption markets, pointing to the importance of retail settings as socio-material spaces for their enactment.